Current career perspective of pediatric cardiologists in India - Sakshi Sachdeva; Bhargavi Dhulipudi (Wolters Kluwer Medknow Publications, 2023)
A survey was conducted to ascertain the current situation of early-mid-career pediatric cardiologists (<20 years of experience) practicing in India. A formatted questionnaire was sent as a Google Form through email and WhatsApp link. Out of 275 eligible participants, 138 responses were received. Two pediatric cardiologists independently analyzed the data and responses are presented. Results showed pediatric cardiology is not considered a lucrative career option by most of the surveyed Indian pediatric cardiologists. Urgent remedial measures are needed to maintain the recently found momentum in the field in the country.